Studies on Neotropical crickets: Mellogryllus mutus n. gen. et n. sp., an intriguing new genus and species of cricket of the Miogryllae Group (Orthoptera: Gryllidae: Gryllinae: Gryllini: Brachytrupina) from the Brazilian Atlantic Forest - Cadena-Castañeda, Oscar J.; Tavares, Gustavo Costa; Fernandes, José Antônio Marin (Zootaxa, 2022)
A new monotypic genus, Mellogryllus mutus n. gen. et n. sp., is described from the dense ombrophilous forests of the Brazilian coastal Atlantic Forest. This new genus is included within the genus-group Miogryllae due to the structure of the male genitalia. The key for the genera of the Group Miogryllae is also updated. Finally, the morphological particularities of Mellogryllus n. gen. are discussed, such as the presence or absence of tympanum in the different sexes, variation in the number of spurs on the legs, and the modification of the first pair of legs for underground life.